Response of tomato plant on various concentrations and application frequency of gibberellin. Issue 1 (April 2020) - Kasim, N; Syam'un, E; Taufik, N; Haring, F; Dermawan, R; Widiayani, N; Indhasari, F
Abstract: This study aimed to determine the production of tomato plants with the application of gibberellin growth regulators. This research was conducted at the Experimental Farm, Faculty of Agriculture, Universitas Hasanuddin from May to September 2017. The study was conducted in the form of an experiment using a Randomized Block Design as an environmental design and repeated three times. The first factor in this study was gibberellin consisted of four levels, namely 0 mg L −1, 15 mg L −1, 30 mg L −1, and 45 mg L −1, the second factor was the frequency of gibberellins application consisted of three levels, namely once, twice, and three times during the growth of the tomato plant. The results showed that the concentration of gibberellin of 45 mg L −1 applied once produced the fastest fruiting age of 48.92 days after planting (DAP), concentration of 45 mg L −1 gibberellin applied three times during growth showed the lowest number of seeds (21.73 seeds), while the concentration of 30 mg L −1 applied three times resulted in earliest fruit ripe (86.17 DAP).